Global Fairness Unveiled: Navigating Justice in The World Trading System - Tiwari, Asmita (Kathmandu School of Law Review, 2024)
According to the website of World Trade Organization (WTO), there are total 164 members, out of which two third are developing countries (includes, both developed and developing countries) and 35 are Under Developed Countries. WTO is now targeting to integrate 8 Least Developed Countries to its trading system. This shows that, participants under ‘Uniform and Liberalized trade Policy of WTO’ are divergent in many aspects; basically, the capability. Accordingly, the benefit shared by developed countries from the bilateral and multilateral treaty arrangements under WTO, is comparably vast and more efficacious for them than that shared by the Least Developed Countries and Developing Countries. This paper has attempted to analyse the fairness doctrine associated within various aspects of trading practice of WTO. This paper is expected to be significant to understand the importance of justice in world trading. To analyse this, firstly, the implication of doctrine of Fairness as advocated by John Rawls and Amartya Sen have been argued in relation to the world Trade. In this regard, it has analysed whether this fairness advocated by them in domestic institutional order is possible to be invoked at international institutional order. If yes, how they can be integrated in global trading practice. Here, analogy of fairness is made with reference to ‘Difference Principle’ of John Rawls and ‘Capabilities Approach’ of Amartya Sen. Similarly, this paper has attempted to analyse the implication of fairness in pertaining to the major issues of WTO like: Protectionist measures, bargaining power, National Treatment Principle and dispute settlement. Lastly, it has aimed to find out whether, there is special treatment under the Trading policy, meant for developing and least developing economies considering their capability and available resources. To sum up, it is expected to unveil the prospect of justice implication in WTO Trading.